(untitled) (Revista Direito em Debate, 2021)
This is a study about gender inequality in sports, with an interdisciplinary bias between Constitutional Law in dialogue with Gender issues. The research is justified by the existence of discourses that tend to perpetuate gender inequality in the sports world. The objective is to demonstrate these discourses, from a bibliographic review, and the importance of deconstructing them. The following problem is studied: do gender inequalities in sports have biological bases or are they built from the reflexes of a patriarchal society? The hypothesis – wich was confirmed - is that there is a discourse - created in a context of a desire to maintain male power - that contributes to gender inequalities in the sports field. In this sense, there are statements of a supposed incapacity of women that would prevent them from participating in modalities, as well as other barriers to female inclusion, such as questions about their bodies that would run away from a pattern of femininity. For the development of the research, is analysed the ideal of equality is analised, gender issues in the sports universe, as well as entering specificities of sports such as football, rugby and Formula 1. The deductive method was used, in addition to bibliographic and electronic research in theses, books, dissertations, periodicals and news.